An autonomous agent framework for the game "Don't Starve" - Aki, Rodrigo T.; Máximo, Marcos R. O. A.; Nascimento, Mariá C. V. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
Applying AI algorithms to find optimal strategies in games has been a heavily researched subject that had a significant impact on video game development and served as the basis for several applications in the real world. In this paper, we investigate developing an AI agent for a game called “Don’t Starve”, a single-player survival game. The main contribution of this work is a novel agent framework for this game that can survive under the same conditions as a human player. In this regard, the agent uses the game screen as the only source of information and executes actions with mouse and keyboard. After testing the AI capabilities, the agent could identify game objects correctly, plan its next steps, collect important resources, and survive for a few days.